MITIGATION OF THE PENALTY IN THE CRIMINAL OFFENSE OF SERIOUS THEFT IN THE PRACTICE OF THE BASIC COURT IN NIS - Ilić Antanasijević, Anita (Glasnik Advokatske komore Vojvodine, 2022)
The subject analysis of the criminal offense of aggravated theft in the case law of the Basic Court in Nis was performed in two ways, ie through two forms of research: insight into court cases and insight into court statistics, from the annual work report, in the period 2010-2018. The institute of mitigation of punishment, which was analyzed in connection with the mentioned criminal offense, includes two segments of work. Namely, the analysis examined the ratio of the number of reported, accused, convicted and acquitted persons, ie persons whose sentences were reduced, and the application of certain mitigating circumstances was analyzed, which the court assessed when mitigating the sentence.When it comes to the application of certain mitigating circumstances, which the court assessed when mitigating the sentence, the investigation took into account the following circumstances: a) age of the defendant, b) property status of the defendant, c) personal circumstances of the defendant, d) family circumstances of the defendant, e) previous conviction of the defendant, f) holding the perpetrator after the crime, e) the relationship of the defendant with the injured party, h) confession of the crime, i) remorse of the defendant and i) health condition of the defendant. The aim of the research was to analyze the application of the observed institute in practice with the application of scientific methods, pointing out the existing problems in its implementation, in order to potentially eliminate them and possibly solve them in practice.